Crystalline deposits in the macula – tamoxifen maculopathy or macular telangiectasia? - Rijal, Roshija Khanal; Nakhwa, Dr Chinmay; Manavi D Sindal, Manavi D Sindal D (Nepalese Journal of Ophthalmology, 2014)
Introduction: Tamoxifen citrate is an anti-estrogen agent used in the treatment of breast carcinoma. Crystalline maculopathy is a rare complication of tamoxifen therapy. The clinical picture resembles that of idiopathic macular telangiectasia (IMT) Type 2, which is a more common clinical entity. Objective: To report a case of crystalline maculopathy secondary to tamoxifen and highlight the importance of the medical history and investigations in differentiating it from IMT Type 2. Case: A diabetic female with a past history of breast carcinoma treated with tamoxifen came to the hospital for a routine eye check-up. Crystalline deposits were seen in the parafoveal region in both the eyes. The spectral domain optical coherence tomography (SD-OCT) showed foveal cysts in the inner retinal layer and fundus autofluorescence (FAF) and fundus fluorescein angiography (FFA) were within normal limits. Conclusion: While tamoxifen maculopathy is reversible on stopping the therapy, IMT needs a long-term follow-up to monitor the potential risk of loss of vision due to choroidal neovascularization, hence necessitating the distinction between these two different clinical entities. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11713 Nepal J Ophthalmol 2014; 6 (12): 227-229